LEADERSHIP STYLES OF PRINCIPALS, A CATALYST FOR CULTIVATING RESEARCH CULTURE: SCIENCE MAPPING OF PRESENT AND FUTURE TRENDS - Wan Ibrahim, Wan Mohd Khairi; Hussain, Suhaidah; Osman, Azim Azuan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study reviews leadership styles adopted by principals in school for fostering research culture. Leadership styles is a major contribution in landscaping schools including innovations and creativity environment. However, there has been no comprehensive understanding of knowledge structure in leadership styles adoption among principals in cultivating research culture in their institution holds in the literature. Through a bibliometric approach, 375 publications on leaderships styles adoption on innovation were retrieved from the Web of Science (WoS). A bibliographic coupling and co-word analysis were performed to uncover past and predict future trends in this regard. The analysis yields noteworthy themes concerning transformational leadership, instructional leadership, and distributed leadership, emphasizing their influence on fostering a strong research-oriented culture in schools. Additionally, the study identifies emerging trends and gaps in the current literature, offering insights into future research directions. The findings suggest that adopting a strategic combination of these leadership styles can effectively foster research activities, drive innovation, and support sustainable academic development. This study provides a foundational framework for educational policymakers and school leaders aiming to foster a vibrant research-oriented environment, ultimately contributing to the advancement of educational practices and outcomes.